The Perception of Witchcraft among the Digo Community of Mtongwe - Mukhwana, Mohammed Amedo; Awadh, Ali Hemed (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
This study examined the perception of witchcraft at the Coast of Kenya focusing on the Digo Community of Mtongwe. The aim of the study was to analyze how witchcraft is perceived among the Digo community of Mtongwe area. Through a qualitative research design, data were gathered using personal interviews and questionnaires with 25 local leaders of the area. The major findings that emerged were: 1. Witchcraft practice is a reality in the area. 2. It also established that the belief in and practice is strong among the youth, especially the female and 3.That witchcraft is practiced for various reasons among them jealousy, protection, love, material wealth, for healing among other reasons. The study concluded that some members of the Digo community still maintain their indigenous belief in and practice of witchcraft despite many years of Islamization. This means that these Digo still have and maintain trust in their traditional worldview more than in popular Islamic worldview about power and influence of sorcery.